Al-Ta’līf Approach to the Implementation of Da‘wah According to an Islamic Perspective - Majid, Mariam Abd.; Abdul Rahman, Aisyah Humairak; Usman, Abur Hamdi; Murghayah, Siti Khaulah Mohd Hamzah; Ismail, Safinah (Jurnal Dakwah Risalah, 2024)
A positive initial perception is able to influence the acceptance of the da‘wah target towards the da‘wah efforts carried out. Islam advocates a variety of al-ta’līf approaches aimed at bringing the target of da‘wah closer to the teachings of Islam. However, in some situations, efforts to deliver da‘wah today are seen to ignore the aspects of al-ta’līf advocated by Islam. Neglecting the al-ta’līf approach in the implementation of da‘wah has been found to threaten the harmony in the relationship between Muslims and non-Muslims, and even in certain situations, can scratch the image of Islam. This article aims to present the approaches of al-ta’līf in the implementation of da‘wah according to the Islamic perspective. Research data was obtained through documentation and content analysis methods. Findings found that the implementation of the al-ta’līf approach in da‘wah needs to be applied in actions, words and writing in line with the recommendations of Islam. This discovery is expected to be used as a guide in the implementation of da‘wah while upholding the image of Islam as the most perfect religion.